2006
DOI: 10.1002/ccd.20896
|View full text |Cite
|
Sign up to set email alerts
|

Successful device closure of an acquired Gerbode defect

Abstract: Left ventricle to right atrial communications, collectively known as Gerbode defects, are usually congenital defects and surgical closure remains the treatment of choice. We report a rare case of Gerbode defect acquired following surgical closure of a ventricular septal defect. The defect was successfully closed percutaneously with an Amplatzer ventricular septal occluder. The patient remained symptom free with optimal result on echo at 6 months of follow-up. This is the first reported case of successful devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 10 publications
(14 reference statements)
1
37
0
1
Order By: Relevance
“…The first successful series of patients operated on with a left ventricular to right atrial shunt was reported by Gerbode et al . There are a few case reports of percutaneous closure of acquired Gerbode shunts . There is a small series of four cases of post‐surgical Gerbode defects closed successfully with various devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first successful series of patients operated on with a left ventricular to right atrial shunt was reported by Gerbode et al . There are a few case reports of percutaneous closure of acquired Gerbode shunts . There is a small series of four cases of post‐surgical Gerbode defects closed successfully with various devices.…”
Section: Discussionmentioning
confidence: 99%
“…These shunts are traditionally closed surgically with high incidence of complete heart block. There are case reports and small series of mostly acquired and few congenital Gerbode defects closed percutaneously with various types of devices . We report a small series of 12 cases of only congenital Gerbode defects closed with Amplatzer duct occluder II (ADO II) which is specially designed to close long tubular duct in infants.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is the treatment of choice; however, percutaneous closure with septal occluders has been used as an alternative. 10,11 Sinisalo and colleagues 10 and Rothman and associates 12 reported using Amplatzer Duct, VSD, and ASD Occluders that had waist diameters slightly larger than the diameters of their patients' Gerbode defects. In our patient, closure with use of a 7-mm AVP IV device failed; an 8-mm Amplatzer VSD Occluder better fit the anatomy of the defect.…”
Section: Discussionmentioning
confidence: 99%
“…Hemolysis has been described in patients after the device closure of VSD and PDA 5)7). As thrombus formation is an important complication as well, we started providing aspirin.…”
Section: Discussionmentioning
confidence: 99%